On Local Non-Global Minimizers of Quadratic Optimization Problem with a Single Quadratic Constraint. (10th June 2020) - Taati, Akram; Salahi, Maziar
Abstract: In this paper, we consider the nonconvex quadratic optimization problem with a single quadratic constraint. First we give a theoretical characterization of the local non-global minimizers. Then we extend the recent characterization of the global minimizer via a generalized eigenvalue problem to the local non-global minimizers. Finally, we use these results to derive an efficient algorithm that finds the global minimizer of the problem with an additional linear inequality constraint.